The Phillips Curve at the ECB - Fabian Eser; Philip Lane; Laura Moretti; Chiara Osbat; Peter Karadi (ZBW - Leibniz Information Centre for Economics, 2020)
We explain the role of the Phillips Curve at the ECB in the analysis of the economic outlook and the formulation of monetary policy. First, revisiting the structural Phillips Curve, we highlight the challenges in recovering structural parameters from reduced-form estimates and relate the reduced-form Phillips Curve to (semi-)structural models used at the ECB for policy analysis. Second, we identify the slope of the structural Phillips Curve following two approaches: one that exploits cross-country variation and the other using high-frequency monetary policy surprises as external instruments. Third, we present reduced-form evidence based on thick-modelling and dynamic model averaging techniques, focusing on the relation between slack and in ation and the role of in ation expectations. In relation to the recent weakness of in ation, we discuss the role of firm profits in the pass-through from wages to prices and the contribution of external factors. Overall, the available evidence supports the view that the absorption of slack and a firm anchoring of in ation expectations remain central to successful in ation stabilisation.
Keywords: E31; E52; 330; Inflation; Phillips Curve; Monetary Policy; European Central Bank